Experience of Managing Urogenital Fistula - Pradhan, HK; Dhangal, G; Karki, A; Shrestha, R; Bhattachan, K (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: The study was done to review the demography of urogenital fistulae including obstetric fistula (OF) and its surgical outcome in the early phase of fistula surgery and to create awareness about OF. Methods: This was a retrospective study of 47 patients who underwent fistula surgery during the period of January 2012 to May 2014 in Kathmandu Model Hospital, Helping Hand Community Hospital, Camp in Mid-wetern Regional Hospital Surkhet and Hamlin Hospital, Ethiopia. The primary outcome was in terms of urinary continence after 14 days of repair. Results: In the study 70% (n=33) of fistula were due to obstructed labour and 30% (n=14) were due to hysterectomy for gynecological indications. Ninety six percent (n=45) had successful closure of fistula. Seventy seven percent (n=36) were continent after surgery, and 17% (n=8) had some stress incontinence. Conclusions: The study showed obstructed labour was the major cause of OF, however iatrogenic fistula was also becoming common. The success of repair depended on the type, site, size of fistula and urethral length. Majority of our cases had successful closure of fistula with some degree of stress in some patients. DOI: http://dx.doi.org/10.3126/njog.v9i1.11181 NJOG 2014 Jan-Jun; 2(1):17-20